BDNF/TrkB signaling in stable coronary artery disease - O. V. Atamas; M. V. Antonyuk; T. P. Novgorodtseva; T. A. Gvozdenko; O. Yu. Kytikova (Российский кардиологический журнал)
Aim. To study the serum content of brain-derived neurotrophic factor (BDNF) and tyrosine kinase receptor B (TrkB) in patients with coronary artery disease (CAD) and evaluate the relationship of BDNF/TrkB signaling with the severity of coronary atherosclerosis, systemic inflammation (IL-2, IL-4, IL-6, IL-10, TNF-α) and angiogenesis (VEGF).Material and methods. The study included 99 patients with stable CAD who underwent coronary angiography and 30 healthy volunteers. Coronary atherosclerosis was assessed using the Gensini score (GS). In blood serum, the concentrations of BDNF, TrkB, VEGF, IL-2, IL-4, IL-6, IL-10, TNF-α were determined using the enzyme immunoassay. Cluster, correlation, and regression analyzes were used.Results. In patients with CAD, a wide range of variations in BDNF concentrations was observed. To determine homogeneous groups using the k-means clustering, three clusters with different BDNF/TrkB axis vectors were identified. Patients differed in the severity of coronary atherosclerosis, the manifestation of the inflammatory reaction, and the intensity of angiogenesis. In patients with initial and moderate atherosclerotic changes in the coronary arteries, a normal concentration of BDNF and an increased level of TrkB (22,35/1,18 ng/ml) were noted. In patients with severe coronary atherosclerosis, two different BDNF/TrkB variants have been identified. Decreased BDNF and increased TrkB (6,0/1,52 ng/ml) were associated with low VEGF and increased IL-6. Elevated BDNF and normal TrkB values (26,95/0,96 ng/ml) were characteristic of patients with high VEGF expression, indicating angiogenesis activation and/or vulnerable plaques. A direct relationship between BDNF and VEGF (r=0,536, p<0,001) and an inverse relationship with TrkB (r=-0,301, p=0,019), IL-6 (r=-0,306, p=0,002) was revealed. TrkB levels were correlated with TNF-α (r=0,403, p=0,001). Regression analysis showed that BDNF expression is influenced by TrkB (β=-0,237, p=0,009), VEGF (β=0,490, p<0,001), IL-6 (β=-0,339, p<0,001).Conclusion. In patients with stable CAD, different levels of BDNF/TrkB expression were found, which were associated with coronary atherosclerosis severity. BDNF/TrkB signaling is involved in the regulation of inflammation and angiogenesis in stable CAD.